A Comparison of QTc Intervals in Alcohol Withdrawal Patients Versus Acute Coronary Syndrome Patients. Issue 7 (July 2017) - Chu, Timothy; Azevedo, Keith; Ernst, Amy A.; Sarangarm, Dusadee; Weiss, Steven J.
Abstract : Objectives: Patients with an alcohol use disorder experiencing acute intoxication or withdrawal may be at risk for electrocardiograph (ECG) abnormalities, including prolongation of repolarization (long QTc [corrected QT]) that may contribute to arrhythmias and may be associated with a threefold increase in the likelihood of sudden cardiac events. Patients with acute coronary syndrome may have prolonged QTc as well. To our knowledge, no previous studies have compared the QTc of ACS with acute ethanol (EtOH) withdrawal syndromes in the emergency department (ED). The purpose of our study was to compare the QTc of those with EtOH withdrawal emergencies with patients with ACS in our ED. Our hypothesis was that the QTc would be similarly prolonged in the two cohorts. Methods: The study compared two cohort groups, those with ACS and those with EtOH withdrawal–related ED visits over a 1-year period. We compared ECG QTc, cardiac medication use, and electrolyte differences. We considered a QTc of >450 ms elevated for men and >470 ms elevated for women based on the literature. Fifty subjects in whom an ECG, serum osmolality, and EtOH level were recorded within 2 hours of one another and who were administered a Clinical Institute Withdrawal Assessment protocol were compared with 203 patients with ACS during the same period. We excluded patients with incomplete data. Medications compared included clopidogrel, acetylsalicylic acid, β-blockers, angiotensin-converting enzyme inhibitors, and statins. ECG QT and QTc, as well as electrolytes, were recorded and compared. Data were extracted by two investigators with a 20% sample re-evaluated by the other extractor as a reliability measure. Descriptive statistics including medians and interquartile ranges were measured for continuous variables. Comparisons were made using two-tailed t tests for parametric data and the Mann-Whitney U test for nonparametric data. Results: Agreement in the 20% sampling between investigators was high (96%). The mean QTc in the ACS group was 457 ms and the mean QTc in the EtOH withdrawal–related group was 468 ms (diff 11, not significant). Significantly more patients had a prolonged QTc in the EtOH withdrawal group than in the ACS group 62% vs 46%; diff 16; 95% CI (0.1, 30). There was significantly more use of clopidogrel, acetylsalicylic acid, angiotensin-converting enzyme inhibitors, and statins ( P < 0.05 for all) in the ACS group compared with the EtOH withdrawal group; however, there was no difference in β-blocker usage. There was a significantly higher admission rate: 100% of ACS compared with 76% of the EtOH withdrawal group ( P < 0.01, diff 24, 95% confidence interval 18–29). Electrolytes were not significantly different in the two groups. Conclusions: More patients with EtOH withdrawal–related ED visits had a long QTc than patients presenting with ACS. ED physicians should carefully monitor patients experiencing EtOH withdrawal for cardiac arrhythmias and obtain an ECG. If any medications that prolong the QTc are considered, then an ECG should be obtained before administering medications that may affect the myocardium to make medication safer for the patient.